Therapeutic play as a qualitative data generation method: A critical reflection - Yolanda Havenga (AOSIS, 2019)
Background: Child-centred research requires researchers to develop research designs that will enable children to express their views in an ethical, appropriate and child-friendly manner and generate rigorous findings. These requirements challenge researchers to develop new methods to generate data with children, and the 'younger the child, the more intense the challenge'. Aim: The aim of this article was to describe and reflect on the use of therapeutic play as a data generation method by nurse researchers with young children in a child-centred qualitative, explorative, descriptive and contextual study using a multiple case study strategy. Setting: The study was conducted with young children attending an outpatient department at a public hospital in Gauteng. Methods: Four young children, purposively sampled, participated in six sessions, each based on therapeutic play grounded in the work of Oaklander's Gestalt play therapeutic approach, facilitated by a nurse researcher. Critical reflection was made about the play therapeutic approach as a data generation method, based on its ability to generate useful data, its implications for data analysis and its ability to be child-enabling and child-centred. Results: The play therapeutic approach, as a data generation method, is capable of generating useful data and amplifying children's voices in the process. Conclusions: The nurse researcher needs to be highly skilled in this approach as it requires the ability to implement the specific play therapeutic approach in a safe and skilful manner.